Variation in tiered network health plan penetration and local provider market characteristics - Sinaiko, Anna D.; Curto, Vilsa E.; Bambury, Elizabeth; Soto, Mark J.; Rosenthal, Meredith B. (Health services research, 2024)
Objective To understand variation in enrollment in tiered network health plans (TNPs) and the local provider market characteristics associated with TNP penetration. Data Sources and Study Setting We used 2013–2017 Massachusetts three‐digit ZIP code level employer‐sponsored health insurance enrollment data, data on physician horizontal and vertical affiliations from the Massachusetts Provider Database, state hospital reports in 2013, 2015, and 2017, and the 2013–2017 Massachusetts All‐Payer Claims database. Study Design Linear regressions were used to estimate associations between TNP and local provider market characteristics. Data Extraction We constructed measures of TNP penetration and local provider market characteristics and linked these data using three‐digit ZIP code. Principal Findings TNP penetration was at least 10% in all employer market sectors and highest among jumbo sized employers. All state employee health plan enrollees were in a tiered network health plan. Among enrollees not in the state employee health plan, TNP penetration varied from 6.0% to 19.6% across three‐digit ZIP codes in Massachusetts. TNP penetration was higher in areas with less horizontal and vertical physician market concentration. Conclusions Market competition, rather than the absolute quantity of physicians in an area, is associated with TNP penetration.